2022
DOI: 10.3389/fgene.2022.963184
|View full text |Cite
|
Sign up to set email alerts
|

Potential regulatory role of miRNA and mRNA link to metabolism affected by chronic intermittent hypoxia

Abstract: Aim: Intermittent hypoxia (IH) is the prominent feature of obstructive sleep apnea (OSA) pathophysiology, which is an in dependent risk factor of cardiovascular complications. The effects of IH on adipocyte metabolism were explored by high-throughput sequencing technology.Methods: Plasma was collected from OSA patients and control group to perform mRNA sequencing. 3T3-L1 cells were differentiated into adipocytes then subjected to a 5%–21% O2 hypoxic environment (IH) for 24 h. High-throughput sequencing method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…As it reported that MAPK signaling that chronic intermittent hypoxia regulated the onset and progression of the disease and drug e cacy via the MAPK pathway [30,31], implying that MAPK signaling may be involved in the evolution and development of various diseases under intermittent hypoxia. In addition, enriched pathways such as the cAMP pathway and PI3K/AKT pathway are also reportedly involved in chronic intermittent hypoxia regulating pathophysiological processes in Atherosclerosis and adipocyte metabolism [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…As it reported that MAPK signaling that chronic intermittent hypoxia regulated the onset and progression of the disease and drug e cacy via the MAPK pathway [30,31], implying that MAPK signaling may be involved in the evolution and development of various diseases under intermittent hypoxia. In addition, enriched pathways such as the cAMP pathway and PI3K/AKT pathway are also reportedly involved in chronic intermittent hypoxia regulating pathophysiological processes in Atherosclerosis and adipocyte metabolism [32,33].…”
Section: Discussionmentioning
confidence: 99%